Characterization of Shikonin Derivative Secretion in Lithospermum erythrorhizon Hairy Roots as a Model of Lipid-Soluble Metabolite Secretion from Plants - Tatsumi, Kanade; Yano, Mariko; Kaminade, Kenta; Sugiyama, Akifumi; Sato, Mayuko; Toyooka, Kiminori; Aoyama, Takashi; Sato, Fumihiko; Yazaki, Kazufumi (Frontiers in Plant Science, 2016)
Shikonin derivatives are specialized lipophilic metabolites, secreted in abundant amounts from the root epidermal cells of Lithospermum erythrorhizon. Because they have anti-microbial activities, these compounds, which are derivatives of red naphthoquinone, are thought to serve as a chemical barrier for plant roots. The mechanism by which they are secreted from cells is, however, largely unknown. The shikonin production system in L. erythrorhizon is an excellent model for studying the mechanism by which lipophilic compounds are secreted from plant cells, because of the abundant amounts of these compounds produced by L. erythrorhizon, the 0 to 100% inducibility of their production, the light-specific inhibition of production, and the visibility of these products as red pigments. To date, many factors regulating shikonin biosynthesis have been identified, but no mechanism that regulates shikonin secretion without inhibiting biosynthesis has been detected. This study showed that inhibitors of membrane traffic strongly inhibit shikonin secretion without inhibiting shikonin production, suggesting that the secretion of shikonin derivatives into the apoplast utilizes pathways common to the ADP-ribosylation factor/GTPase-activating protein (ARF/GAP) system and actin filament polymerization, at least in part. These findings provide clues about the machinery involved in secreting lipid-soluble metabolites from cells.